2016
DOI: 10.1111/iej.12622
|View full text |Cite
|
Sign up to set email alerts
|

Influence of N‐methyl pyrrolidone on the activity of the pulp–dentine complex and bone integrity during osteoporosis

Abstract: N-methyl pyrrolidone (NMP) had a remarkable anti-osteoporotic ability preserving activity in the pulp-dentine complex and preventing jawbone loss. These effects make NMP a promising candidate for the preservation of the activity of the pulp-dentine complex and jawbone thickness in post-menopausal females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…[ 23 ] reported that NMP contained in a drug delivery system for Leuprolide did not exhibit significant toxicity in mice. Recently, it was found that NMP has some biologic activity on the pulp-dentin complex as well as bone metabolism [ 24 ], and it is suggested as a promising vehicle for bone morphogenic protein (BMP) and enhances the bone regeneration effect [ 25 ]. Nevertheless, there are some controversies regarding the cytotoxicity of NMP.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] reported that NMP contained in a drug delivery system for Leuprolide did not exhibit significant toxicity in mice. Recently, it was found that NMP has some biologic activity on the pulp-dentin complex as well as bone metabolism [ 24 ], and it is suggested as a promising vehicle for bone morphogenic protein (BMP) and enhances the bone regeneration effect [ 25 ]. Nevertheless, there are some controversies regarding the cytotoxicity of NMP.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of the BRD target osteoblastogenesis via Runx2 inhibition and osteoclastogenesis via inhibition of Myc and nuclear factor kappa B (NFκB) [ 102 ]. In the context of the treatment of osteoporosis and bone loss, BRD inhibitors have shown in vitro and in vivo promising results presumably due to their activity to inhibit osteoclastogenesis and inflammation [ 98 , 102 , 103 , 104 , 105 , 106 , 107 ]. Indeed, DNA methylation and histone modifications such as acetylation could be recognized by BRD-containing proteins and selective BRD inhibitors seem to be a new epigenetic approach to treat bone-related diseases.…”
Section: Epigenetically Active Drugs and Bone Homeostasismentioning
confidence: 99%
“…Alternatively, the periodic injection of NMP can also be considered because NMP is an injectable pharmaceutical excipient in FDA-approved formulations. A weekly injection of NMP was previously shown to produce antiosteoporotic activity in ovariectomized rats [22, 23]. However, those authors stated that the frequency and duration of the injections need be investigated further.…”
Section: Discussionmentioning
confidence: 99%